The six new rules of business : creating real value in a changing world - Samuelson, Judy (Berrett-Koehler Publishers, Inc., 2021)
"The rules of business are changing dramatically. The Aspen Institute's Judy Samuelson describes the profound shifts in attitudes and mindsets that are redefining our notions of what constitutes business success"--